University Success Histories of Autistic Graduates: An Ecological Analysis of Personal and Contextual Factors - Van der Mel, Lucía; Moriña, Anabel (Pedagogika, 2024)
This article aims to understand the personal and contextual factors con- tributing to university retention for autistic graduates. In addition, it examines graduates’ evaluations of their own trajectories, shaped by their reflexive interpretations of university success. To achieve this, the study employs a biographical narrative approach. The results are presented through five polyphonic life histories holistically reflecting their university journeys.